Market integration and international portfolio diversification from Malaysian perspective / Surianor Binti Kamaralzaman - Surianor, Kamaralzaman (2011)
The purpose of this thesis is to investigate a comprehensive, concurrent comparison of the potential benefits of international diversification between Malaysian markets and developed and developing countries from the viewpoint of a Malaysian investor. Specifically, it bridges the theory between the cointegration methodology and international benefits of diversification by linking market integration, cointegration and portfolio diversification. This study takes a two-fold approach to investigate the issue of market integration from the perspective of a Malaysian investor who would diversify internationally with world global markets. First, the short and long run co-movements with the Malaysian market of twenty-one of the most developed and developing equity markets in the world are examined by employing econometric methodology and utilizing standard cointegration analysis. Second, mean variance analysis and the construction of a portfolio are employed to form efficient frontiers, providing the basis for recommending the degree of diversification into the Malaysian equity market. To facilitate a more comprehensive investigation, this study is divided into four sub periods to capture the effects on the Malaysian market of various stages. In addition, closing daily MSCI indices are used and the influence of financial crisis are also analysed by contrasting different periods from 1996-2007. In general, the research findings of the study are mixed in relation to the issues discussed in this study. Taking into account entire periods, pre crisis, crisis and post crisis period, some findings of the short-run and long-run causal influences and the portfolio constructions, which can be summarized. Our findings suggest, that between Malaysia and the developed markets, there were long-run relations between the developed and Malaysian market during the pre crisis and post crisis period, which indicates that obtaining abnormal profits through portfolio diversification is limited in the long-run. However, there are substantial short-run dynamic interactions between the developed and the Malaysian market for all sub periods. Moreover, the results suggest that long-run relationships among all the markets under consideration were altered by the crisis and were actually strengthened. In addition, the Malaysian market has either unidirectional or bidirectional Granger causality with the US, Japan and Hong Kong in all sub periods. There is less bidirectional relationships between the developed markets and the Malaysian market during the pre crisis and crisis period, as compared to the post crisis period. We also found that the developed countries (larger economies) are higher degree Granger cause developing (smaller economies) countries. In contrast, the variations in the Malaysian market respond more to shocks in the US, Japan and Hong Kong during the overall period, crisis period and post crisis period. In contrast, between the Malaysian and developing markets, one general conclusion that can be drawn from this long run relationship is that the developing stock markets were moving towards a greater integration either among themselves or with the Malaysian market during the crisis period and were weakened after the crisis. Our findings further imply that there was room to gain benefit from the international investment diversification to be earned by investors across developing stock markets in the post financial crisis period as the markets tended to be weaker. There appear to be extensive short-run dynamic interactions between the developing and Malaysian market in the short-run. In addition, relatively, the Argentinean market was found to have no causalities with the Malaysian market for all periods. Therefore, Malaysian investors would have much scope to include the stock of Argentina as it has maximal benefits of diversification. Whereas, the Indian market, for example, significantly Granger caused the Malaysian market during all the sub periods except the crisis period. Furthermore, the investment proportion of optimal portfolios for various interest rates between Malaysia with the developed and developing markets under consideration are different for all sub periods. In addition, it can be clearly seen that the efficient frontiers of the Malaysian and developing countries for the pre crisis and post crisis are generally superior than those for during the overall period and crisis period. An important implication of our findings is that the degree of integration among developed and developing countries tends to change over time, especially around periods marked by financial crisis. Furthermore, for policymaking, any disturbances in the markets of the US, Japan, Hong Kong or India should be taken into consideration by the Malaysian authorities in designing policies that has repercussions on the Malaysian market.